An Analysis of Grammatical Cohesian on Barack Obama Speech: Discourse Analysis - Mantiri, Ruben Leopoldo; Rudianto, Gaguk (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2024)
This qualitative research study explores the types of grammatical cohesiveness frequently used in utterances, focusing on the relationship between theory and research as proposed by Halliday and Hasan (1976). The research data is derived from former President Barack Obama’s farewell speech, available on The Obama White House YouTube channel since January 11, 2017. The primary objective is to examine the presence and usage of ellipsis, reference, conjunction, and substitution in Obama’s speech. Data collection employed an observational approach, with researchers watching and listening to the speech while taking notes. The analysis process involved understanding the context and categorizing the data based on Halliday and Hasan’s theoretical framework, with findings presented using descriptive statistics. The study identified significant occurrences of grammatical cohesiveness, including 15 references, 10 substitutions, 4 conjunctions, and 9 ellipses in Obama’s speech. These cohesive elements are instrumental in ensuring effective communication and message integration, enabling the audience to follow the speech seamlessly. By investigating grammatical cohesiveness in Obama’s farewell address, this research contributes to the understanding of how theory and research interact within language use and highlights the importance of cohesive linguistic elements in conveying messages effectively.